Anaerobic external combustion thermal engines - V. I. Karagusov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
Anaerobic engines are air-independent engines used in rocket and space technology, in submarines and in regular public service facilities. In rocket and space technology, liquid and solid rocket and jet engines are used. In open and underwater facilities, anaerobic nuclear-powered engines are used, as well as diesel engines with internal combustion with fuel reserves and oxidizing agents, often in cryogenic form. Internal combustion engines with all their advantages have several disadvantages. External combustion engines based on pulsation pipes and thermoacoustic effect are promising for orbital, rocket, underwater onboard and autonomous power plants. They may lack mechanical parts and assemblies, which determines long life, high reliability, minimal noise and vibrations. To operate such engines can use any fuel, they practically do not require maintenance